PENGARUH CAPITAL DAN CAPACITY TERHADAP PEMBERIAN KREDIT - Dion Yanuarmawan (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2013)
BPR Tanjung Tani represent the institute intermediasi to owning fund and require the fund from society. One of the product BPR Tanjung Tani is credit channelled to client. Problem of credit which often emerge is the existence of NPL (non performance loan) or credit height stuck. For that need the carefulness in channelling credit to client so that to be credit channelled improve the benefit to client. The Carefulness approach done/conducted with the analysis of elegibility of giving credit to client through the analysis capital and capacity. Result of this research, indicate that capital and capacity influence significant to credit channelled.